Genome-Wide Identification of DOG1 Domain Containing Proteins and Their Role in Moisture Deficit Stress Tolerance in Tomato - Hara Gopal Krishnajee; Senthil Kumar Avinash; Dayanandhi Elangovan; Malarvizhi Mathiazhagan; Avvaerahally Thammannagouda Sadashiva; Laxman Ramanna Hunashikatti; Kumudini Belur Satyan; Kundapura V. Ravishankar (Plant Molecular Biology Reporter, 2026)

Genome-wide association study identifies significant SNPs for milk production and stature traits in Karan Fries cattle - Pritam Pal; Ishmeet Kumar; Manisha Choudhary; Amritanshu Upadhyay; Irusappan Ilayaraja; Anil Chitra; Lal Muansangi; Gopal Gowane; T. V. Raja; Anupama Mukherjee; Sabyasachi Mukherjee (Mammalian Genome, 2026)

Ecosystem spectral fingerprinting and geospatial evaluation of hydrological and vegetation dynamic processes in the Bhavani River Basin, Southern India - S. Zuvairiya; S.R. Singarasubramanian; A. Bobby Jones; V. Gopal (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Distribution and Ecological Risk of Microplastics Across Air, Water, and Soil in a Coastal Megacity of Southern India - M. Bhuvaneswari; Anju Maria Joseph; S. Yamini; M. Suresh Gandhi; V. Gopal (Water, Air, & Soil Pollution, 2026)

Integrated Transcriptomic and Small RNA Profiling Reveals Regulatory Networks Associated With Seed Protein Accumulation in Chickpea (Cicer arietinum L.) - Gopal Kalwan; Deshika Kohli; Yashwant Kumar Yadava; Sheel Yadav; Suruchi Khanna; Ila Joshi; MS Nimmy; S. V. Amitha Mithra; Biswajit Mondal; Shailesh Tripathi; Satvir Kaur Grewal; Kishor Gaikwad; et al. (Journal of Plant Growth Regulation, 2026)

Integrated experimental, statistical, and ANN validation study on concrete deterioration under acid rain, carbonation, and chloride environments - Y. H. Sudeep; V. Vijaykumar; M. S. Ujawl; Christo George; S. Karthik; Rakesh Kumar; Gopal Bharamappa Bekkeri; Kiran K. Shetty (Innovative Infrastructure Solutions, 2026)
Concrete structures in coastal–industrial regions are simultaneously exposed to acid rain, carbonation, and chloride ingress; however, most durability studies investigate these mechanisms independently, limiting realistic service-life prediction. This study presents an integrated experimental, statistical, and artificial neural network (ANN)-based evaluation of M40-grade concrete subjected to synthetic acid rain, accelerated carbonation, and combined carbonation–chloride environments. Laboratory simulations were conducted for exposure durations of 20, 40, 60, and 80 h to replicate aggressive atmospheric conditions. Mechanical degradation was assessed through compressive and splitting tensile strength tests, while chemical deterioration was quantified using depth-wise pH profiling and carbonation depth measurements. Results revealed that compressive strength decreased by up to ~ 25% under acid rain exposure and showed greater deterioration under combined carbonation–chloride conditions. Splitting tensile strength exhibited higher sensitivity to degradation, with reductions exceeding 20% at prolonged exposure durations. Surface pH declined from 12.6 to approximately 8.8, confirming rapid alkalinity loss in the outer 1 cm zone. Carbonation depth increased progressively, reaching ~ 11.5 mm in the combined exposure environment. Regression analysis demonstrated strong inverse correlations (R 2 > 0.90) between carbonation depth and mechanical properties, while one-way ANOVA confirmed statistically significant differences across exposure durations ( p < 0.05). To enhance predictive capability, an ANN model was developed using experimental parameters as inputs, achieving high prediction accuracy (R 2 = 0.98 for training and R 2 = 0.96 for testing). The findings highlight synergistic deterioration effects of multi-environmental exposure and emphasize durability-based design strategies for reinforced concrete structures in aggressive environments.

Quantifying milk production losses due to heat stress in Indian Sahiwal cattle - P. Priyadharshini; Alex Rani; Gowane Gopal; Phoebe C Lalremruati; Vohra Vikas; T. V. Raja (International Journal of Biometeorology, 2026)

Molecular characterization of Phytophthora palmivora associated with black pod rot disease of cocoa in Andhra Pradesh, India - B. Neeraja; V. Prasanna Kumari; K. Gopal; N. B. V. Chalapathi Rao (Indian Phytopathology, 2026)

Radon-thoron exhalation rates in mineral-enriched beach sand of the Chennai coast, India - M. John Samson; K. Manikanda Bharath; A. Vidyasakar; K. Ajith Kumar; V. Arun Bharathi; Satyanarayan Bramha; S. Chandrasekaran; Kannaiyan Neelavannan; V. Gopal; S. Ajith Kumar; N. Sivakumar (Environmental Geochemistry and Health, 2026)

Role of mesoscale eddy on the occurrence of a rare polychaete swarm after five decades in Bay of Bengal waters, northern Indian Ocean - Aiswarya Gopal; Manigandan V.; Sathishkumar R. S.; Logesh Natarajan; Sanitha K. Sivadas; Karri Ramu; R. S. Kankara (Marine Biodiversity, 2026)

Weed Detection Approach for Soybeans Using Fuzzy Ensemble and Image Similarity - G. V. S. Narayana; Sanjay K. Kuanar; Punyaban Patel; S. Gopal Krishna Patro; Ayodeji Olalekan Salau (Journal of Crop Health, 2026)

Genome wide identification, characterization and evolutionary relationship analysis of the Dof gene family in Drumstick plant (Moringa oleifera) - Senthil Kumar Avinash; Malarvizhi Mathiazhagan; Dayanandhi Elangovan; Hara Gopal Krishnajee; Pooja Bharti; Raja Shankar; Laxman R. Hunashikatti; Kundapura V. Ravishankar (Genetic Resources and Crop Evolution, 2026)

Genetic analysis of novel resilience indicators for heat stress-induced milk loss in Indian Sahiwal cattle - P. Priyadharshini; Alex Rani; Gowane Gopal; Mukherjee Sabyasachi; Phoebe C. Lalremruati; Vohra Vikas; T. V. Raja (Tropical Animal Health and Production, 2025)

Afforestation‐Related Fertilisation Quickly Turns Barren Cutaway Peatland Into a Carbon Dioxide Sink - Alexander J. V. Buzacott; Kari Laasasenaho; Risto Lauhanen; Kari Minkkinen; Paavo Ojanen; Gopal Adhikari; Liisa Jokelainen; Lassi Päkkilä; Hannu Marttila; Annalea Lohila (Global Change Biology, 2025)
Energy peat extraction has declined rapidly in Europe in recent years, leaving thousands of hectares of land requiring after‐use management and planning. A popular after‐use option, afforestation, is understudied and there is a limited understanding of its overall effect on greenhouse gas (GHG) and energy exchange. In this study, we present a multi‐year record of eddy covariance fluxes of carbon dioxide (CO 2 ), energy fluxes and surface albedo, chamber measurements of methane (CH 4 ) and (N 2 O), and estimates of lateral carbon (C) losses from dissolved organic carbon (DOC) measurements from a cutaway peatland in Finland during the first 3 years of afforestation. The site was fertilised with wood ash and 2‐year‐old Scots pine ( Pinus sylvestris ) saplings were planted. Wild vegetation emerged at the site in the first summer after fertilisation. Satellite‐derived leaf area index data showed clear year‐on‐year increases, and there was good agreement with changes in CO 2 fluxes over the full study period. The albedo of the site increased with plant cover annually, resulting in negative radiative forcings and net CO 2 ‐equivalent (CO 2 ‐eq) removals. After being a source of CO 2 in the first year (144 ± 20 g CO 2 ‐C m −2 year −1 ), the site transitioned to a sink for the next two study years (−36 ± 12 and −19 ± 19 g CO 2 ‐C m −2 year −1 ). Annual fluxes of CH 4 and N 2 O were small but not negligible. Net annual C losses stopped after 1 year, where DOC losses offset CO 2 uptake, and the afforestation resulted in a mean change in the annual net ecosystem C balance of 172 g C m −2 year −1 and radiative balance of −688 g CO 2 ‐eq m −2 year −1 over a 100‐year time horizon. Cutaway peatlands typically remain long‐term sources of C if abandoned, and our results indicate that the afforestation process can rapidly revegetate barren peatlands and halt net C losses.

Emerging contaminants in urban Soils: Characterization, sources, and environmental impacts of microplastics in southern India - M. Bhuvaneswari; V. Gopal; R. Vinoth; R. Aakash; N.M. Swetha; S. Vinoth kumar; R.R. Krishnamurthy; M.Suresh Gandhi; Renuka Sharma; Ramamoorthy Ayyamperumal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

A coral microatoll record of sea-level rise, interseismic deformation, and El Niño in La Union, Philippines since 1906 CE - Gina M. Sarkawi; Aron J. Meltzner; Dongju Peng; Joanne T.Y. Lim; Xinnan Li; Rohan Gautam; Anandh Gopal; Andrew Mitchell; Loraine Faye Sarmiento; Jennifer Weil-Accardo; Kathrine V. Maxwell; Junki Komori; et al. (Marine Geology, 2025)

Assessment of climate change vulnerability of agriculture in coastal districts of India using principal component analysis and entropy-based methods - Bappa Das; Sonam Sah; K. V. Reddy; S. J. Balaji; Sujeet Desai; Gopal Mahajan; Pooja Singh; Saurav Saha; Uthappa AR; Parveen Kumar; V. K. Sehgal; Ram N. Singh; et al. (Theoretical and Applied Climatology, 2025)

Analysis of Doppler Audio Signals from the Carotid Artery - T. V. Vidya Gopal; Inayathullah Ghori; Avinash Eranki; Annie Qurratulain Hasan; Renu John (Journal of Medical and Biological Engineering, 2025)

Plant diversity and microbial interaction on soil carbon stock in the tropical homegardens: a nature-based solution to climate change - Athulya Tom; V. Divya Vijayan; T. K. Kunhamu; S. Sandeep; K. Surendra Gopal; V. Jamaludheen; B. R. Vishnu (Agroforestry Systems, 2025)

Effects of Soil Application of Nanobiochar-Based Nitrogen and Potassium Fertilizers on the Growth and Yield of Groundnut (Arachis Hypogaea L.) - K. Nagaraju; T. N. V. K. V. Prasad; M. Sreenivasa Chari; Y. Reddi Ramu; B. Ramana Murthy; M. V. S. Naidu; G. P. Leelavathy; P. Ram Mohan; A. G. Damu; D. Gopal (Journal of Soil Science and Plant Nutrition, 2024)

The IAHS Science for Solutions decade, with Hydrology Engaging Local People IN one Global world (HELPING) - Berit Arheimer; Christophe Cudennec; Attilio Castellarin; Salvatore Grimaldi; Kate V. Heal; Claire Lupton; Archana Sarkar; Fuqiang Tian; Jean-Marie Kileshye Onema; Stacey Archfield; Günter Blöschl; Pedro L. Borges Chaffe; et al. (Hydrological Sciences Journal, 2024)

Geochemical evaluation, ecological and human health risk assessment of potentially toxic elements in urban soil, Southern India - V. Gopal; R.R. Krishnamurthy; A. Indhumathi; Beenu T.X. Sharon; T.S. Derlin Priya; K. Rathinavel; K. Manikanda Bharath; N.S. Magesh; Ramamoorthy Ayyamperumal (Environmental Research, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

A global analysis of field body temperatures of active squamates in relation to climate and behaviour - Shahar Dubiner; Rocío Aguilar; Rodolfo O. Anderson; Diego M. Arenas Moreno; Luciano J. Avila; Estefania Boada‐Viteri; Martin Castillo; David G. Chapple; Christian O. Chukwuka; Alison Cree; Félix B. Cruz; Guarino R. Colli; et al. (Global Ecology and Biogeography, 2024)
Aim Squamate fitness is affected by body temperature, which in turn is influenced by environmental temperatures and, in many species, by exposure to solar radiation. The biophysical drivers of body temperature have been widely studied, but we lack an integrative synthesis of actual body temperatures experienced in the field, and their relationships to environmental temperatures, across phylogeny, behaviour and climate. Location Global (25 countries on six continents). Taxa Squamates (210 species, representing 25 families). Methods We measured the body temperatures of 20,231 individuals of squamates in the field while they were active. We examined how body temperatures vary with substrate and air temperatures across taxa, climates and behaviours (basking and diel activity). Results Heliothermic lizards had the highest body temperatures. Their body temperatures were the most weakly correlated with substrate and air temperatures. Body temperatures of non‐heliothermic diurnal lizards were similar to heliotherms in relation to air temperature, but similar to nocturnal species in relation to substrate temperatures. The correlation of body temperature with air and substrate temperatures was stronger in diurnal snakes and non‐heliothermic lizards than in heliotherms. Body‐substrate and body‐air temperature correlations varied with mean annual temperatures in all diurnal squamates, especially in heliotherms. Thermal relations vary with behaviour (heliothermy, nocturnality) in cold climates but converge towards the same relation in warm climates. Non‐heliotherms and nocturnal species body temperatures are better explained by substrate temperature than by air temperature. Body temperature distributions become left‐skewed in warmer‐bodied species, especially in colder climates. Main Conclusions Squamate body temperatures, their frequency distributions and their relation to environmental temperature, are globally influenced by behavioural and climatic factors. For all temperatures and climates, heliothermic species' body temperatures are consistently higher and more stable than in other species, but in regions with warmer climate these differences become less pronounced. A comparable variation was found in non‐heliotherms, but in not nocturnal species whose body temperatures were similar to air and substrate irrespective of the macroclimatic context.

Wound healing activities of PVA–urea composites from Ormocarpum cochinchinense - N. Aarthi; M. Muthuraj; M. Archana; V. Gopal; N. Balasubramanian; S. Rajeswari (Natural Product Research, 2024)

Treatment of waste using waste-derived materials and free energy: A practical concept of circular-economy - Aditi Bhole; Gopal C. Koladia; Shubham P. Koladia; Nisha V. Bora; Leena V. Bora (Sustainable Chemistry and Pharmacy, 2024)

Feasibility of bioplastic production using micro- and macroalgae- A review - Muthiyal Prabakaran Sudhakar; Rahulkumar Maurya; Sanjeet Mehariya; Obulisamy Parthiba Karthikeyan; Gopal Dharani; Kulanthiyesu Arunkumar; Sandra V. Pereda; María C. Hernández-González; Alejandro H. Buschmann; Arivalagan Pugazhendhi (Environmental Research, 2024)

Identification and validation of blast resistance Pi1 gene in the derived mapping population of rice variety, NLR34449 through molecular markers - Dasari Aleena; V. Padma; G. Rekha; M. S. Prasad; M. S. Madhav; E. Punniakoti; T. Dilip; P. Sinha; M. Kousik; M. A. Das; M. Anila; Lal Ahmmed; et al. (Indian Phytopathology, 2023)

Correction to: New Records of Polychaetes from Palk Bay, Bay of Bengal, Northern Indian Ocean - Aiswarya Gopal; Jawed Equbal; Sanitha K. Sivadas; Karri Ramu; M. V. Ramana Murthy (Thalassas: An International Journal of Marine Sciences, 2023)

New Records of Polychaetes from Palk Bay, Bay of Bengal, Northern Indian Ocean - Aiswarya Gopal; Jawed Equbal; Sanitha K. Sivadas; Karri Ramu; M. V. Ramana Murthy (Thalassas: An International Journal of Marine Sciences, 2023)

Microplastic intrusion into the zooplankton, the base of the marine food chain: Evidence from the Arabian Sea, Indian Ocean - Prasun Goswami; Narasimman Selvakumar; Pankaj Verma; Mahua Saha; V. Suneel; Nambali Valsalan Vinithkumar; Gopal Dharani; Chayanika Rathore; Jibananand Nayak (Science of The Total Environment, 2023)

A global analysis of viviparity in squamates highlights its prevalence in cold climates - Anna Zimin; Sean V. Zimin; Richard Shine; Luciano Avila; Aaron Bauer; Monika Böhm; Rafe Brown; Goni Barki; Gabriel Henrique de Oliveira Caetano; Fernando Castro Herrera; David G. Chapple; Laurent Chirio; et al. (Global Ecology and Biogeography, 2022)
Aim Viviparity has evolved more times in squamates than in any other vertebrate group; therefore, squamates offer an excellent model system in which to study the patterns, drivers and implications of reproductive mode evolution. Based on current species distributions, we examined three selective forces hypothesized to drive the evolution of squamate viviparity (cold climate, variable climate and hypoxic conditions) and tested whether viviparity is associated with larger body size. Location Global. Time period Present day. Taxon Squamata. Methods We compiled a dataset of 9061 squamate species, including their distributions, elevation, climate, body mass and reproductive modes. We applied species‐level and assemblage‐level approaches for predicting reproductive mode, both globally and within biogeographical realms. We tested the relationships of temperature, interannual and intra‐annual climatic variation, elevation (as a proxy for hypoxic conditions) and body mass with reproductive mode, using path analyses to account for correlations among the environmental predictors. Results Viviparity was strongly associated with cold climates at both species and assemblage levels, despite the prevalence of viviparity in some warm climates. Viviparity was not clearly correlated with climatic variability or elevation. The probability of being viviparous exhibited a weak positive correlation with body size. Conclusions Although phylogenetic history is important, potentially explaining the occurrence of viviparous species in regions that are warm at present, current global squamate distribution is characterized by a higher relative abundance of viviparity in cold environments, supporting the prediction of the “cold‐climate” hypothesis. The roles of climatic variation and hypoxia are less important and not straightforward. Elevation probably exerts various selective pressures and influences the prevalence of viviparity primarily through its effect on temperature rather than on oxygen concentration.

Autochthonous nutrient recycling driven by soil microbiota could be sustaining high coconut productivity in Lakshadweep Islands sans external fertilizer application - Murali Gopal; Alka Gupta; V. Arunachalam; H. P. Maheswarappa; George V. Thomas; P. M. Jacob (World Journal of Microbiology and Biotechnology, 2022)

63 K and 50 K SNP array based high-density genetic mapping and QTL analysis for productivity and fiber quality traits in cotton - S. Anjan Gowda; Ishwarappa S. Katageri; Rajesh S. Patil; P. Sharat Kumar; Gopal J. Tiwari; Satya N. Jena; Samir V. Sawant (Euphytica, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Variation of salinity in the Sundarbans Estuarine System during the Equinoctial Spring tidal phase of March 2011 - Meenakshi Chatterjee; D Shankar; V Vijith; G K Sen; D Sundar; G S Michael; P Amol; Abhisek Chatterjee; P Sanyal; Siddhartha Chatterjee; Anwesha Basu; Saranya Chakraborti; et al. (Journal of Earth System Science, 2021)

Comparative Evaluation of Patties Prepared from Pacific White Shrimps ( Litopenaeus vannamei ) Grown in Inland Saline Water and Brackish Water Regimes during Frozen Storage - D M Affarin Tinku; K.A. Martin Xavier; Binaya Bhushan Nayak; V. Hari Krishna; Gopal Krishna; Amjad Khansaheb Balange (Journal of Aquatic Food Product Technology, 2021)

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Nine new records of brittle stars (Echinodermata: Ophiuroidea) from Indian waters - Usha V. Parameswaran; Aiswarya Gopal; K. U. Abdul Jaleel; N. Saravanane (Marine Biology Research, 2021)

Management of Fusarium root rot of coriander with chemical and bio‐control agents - M. S. V. Satyanarayana; K. Gopal; Ch. Ruth; S. Sadarunnisa; V. Vijaya Bhaskar (Indian Phytopathology, 2021)

Soil loss hinders the restoration potential of tree plantations on highly eroded ravine slopes - Raj Kumar; A. K. Bhardwaj; B. K. Rao; A. K. Vishwakarma; Vijaysinha Kakade; D. Dinesh; Gaurav Singh; Gopal Kumar; V. C. Pande; P. R. Bhatnagar; G. L. Bagdi (Journal of Soils and Sediments, 2021)

Distinctive Community Patterns With Exceptional Diversity of Polychaetes Around a Tectonically Active Archipelago in the Tropical Indian Ocean - Aiswarya Gopal; K. U. Abdul Jaleel; Usha V. Parameswaran; V. N. Sanjeevan; A. V. Saramma; Anilkumar Vijayan; N. Saravanane; G. V. M. Gupta; M. Sudhakar (Frontiers in Marine Science, 2020)

In silico study of chikungunya polymerase, a potential target for inhibitors - Ritu Ghildiyal; Sanjay Gupta; Reema Gabrani; Gopal Joshi; Amita Gupta; V. K. Chaudhary; Vandana Gupta (VirusDisease, 2019)

Evaluation of Circulating Plasma VEGF-A, ET-1 and Magnesium Levels as the Predictive Markers for Proliferative Diabetic Retinopathy - Gopal Niranjan; A. R. Srinivasan; K. Srikanth; Gowda Pruthu; R. Reeta; Ramasamy Ramesh; Rajendiran Anitha; V. Mohana Valli (Indian Journal of Clinical Biochemistry, 2019)

Identification of Rhizosphere Bacterial Diversity with Promising Salt Tolerance, PGP Traits and Their Exploitation for Seed Germination Enhancement in Sodic Soil - T. Damodaran; V. K. Mishra; S. K. Jha; Umesh Pankaj; Garima Gupta; Ram Gopal (Agricultural Research, 2019)

An updated checklist of echinoderms of the southeastern Arabian Sea - Usha V. Parameswaran; V. N. Sanjeevan; K. U. Abdul Jaleel; Vinu Jacob; Aiswarya Gopal; Anil Kumar Vijayan; M. Sudhakar (Marine Biodiversity, 2018)

Persistence, dissipation and consumer risk assessment of a combination formulation of flubendiamide and deltamethrin on cucumber - K.K. Sharma; V. Shashi Bhushan; Cherukuri Sreenivasa Rao; K. Narsimha Reddy; Hemanta Banerjee; Swagata Mandal; Balwinder Singh; R.S. Battu; Gagan Jyot; S.K. Sahoo; Soudamini Mohapatra; S. Lekha; et al. (Food Additives & Contaminants: Part A, 2018)

Economic assessment of agri-horticulture production systems on reclaimed ravine lands in Western India - V. C. Pande; R. S. Kurothe; Gopal Kumar; H. B. Singh; S. P. Tiwari (Agroforestry Systems, 2018)

Synthesis, antioxidant, and antiviral properties of pyrimidinylsulfamoyl azolyl acetamides - Kuppi Reddy Gari Divya; Donthamsetty V. Sowmya; Suram Durgamma; Vadlamudi Tharanath; Divi Venkataramana Sai Gopal; Malaka Venkateshwarulu Jyothi Kumar; Chippada Appa Rao; Adivireddy Padmaja; Venkatapuram Padmavathi (Medicinal Chemistry Research, 2017)

Changes in structure and function of bacterial communities during coconut leaf vermicomposting - Murali Gopal; Shrikant S. Bhute; Alka Gupta; S. R. Prabhu; George V. Thomas; William B. Whitman; Kamlesh Jangid (Antonie van Leeuwenhoek, 2017)

Transcriptomic and proteomic analysis of yellow mosaic diseased soybean - Bapatla Kesava Pavan Kumar; S. Kanakala; V. G. Malathi; P. Gopal; R. Usha (Journal of Plant Biochemistry and Biotechnology, 2017)

Agricultural innovation and adaptation to climate change: empirical evidence from diverse agro-ecologies in South Asia - Gopal Datt Bhatta; Hemant Raj Ojha; Pramod Kumar Aggarwal; V. Rasheed Sulaiman; Parvin Sultana; Dhanej Thapa; Nimisha Mittal; Khemraj Dahal; Paul Thomson; Laxman Ghimire (Environment, Development and Sustainability, 2017)

Citrus yellow mosaic badnavirus infecting Citrus sp.: a threat to the citrus industry and a quarantine issue - A. M. Anthony Johnson; D. V. R. Sai Gopal; Chinta Sudhakar; Indranil Dasgupta (Journal of General Plant Pathology, 2017)

On an unusual shallow occurrence of the deep-sea brittle star Ophiomyces delata in the Duncan Passage, Andaman Islands (Northern Indian Ocean) - Usha V. Parameswaran; Abdul Jaleel K. U.; Aiswarya Gopal; Sanjeevan V. N.; Anil Kumar Vijayan (Marine Biodiversity, 2016)

Comparative Evaluation of Natural Antioxidant Coating and Vacuum-Packaging Technique on Quality Characteristics of Chill Stored Giant Trevally Fillets - P. K. Binsi; C. N. Ravishankar; S. Suseela Mathew; V. P. Athira; K. B. Biji; C. G. Joshy; T. K. Srinivasa Gopal (Journal of Aquatic Food Product Technology, 2016)

Geochemical study of core sediments from Ennore Creek, North of Chennai, Tamil Nadu, India - V. Gopal; G. Kalpana; S. Nethaji; M. Jayaprakash (Arabian Journal of Geosciences, 2016)

Evaluation of total trace metal (TTMs) enrichment from estuarine sediments of Uppanar, southeast coast of India - G. Kalpana; A. Shanmugasundharam; S. Nethaji; Arya Viswam; R. Kalaivanan; V. Gopal; M. Jayaprakash (Arabian Journal of Geosciences, 2016)

Sequence analysis of Indian iris yellow spot virus ambisense genome segments: evidence of interspecies RNA recombination - S. J. Gawande; V. S. Gurav; A. A. Ingle; D. P. Martin; R. Asokan; J. Gopal (Archives of Virology, 2015)

Diversity, richness and degree of colonization of arbuscular mycorrhizal fungi in coconut cultivated along with intercrops in high productive zone of Kerala, India - P. P. Rajeshkumar; George V. Thomas; Alka Gupta; Murali Gopal (Symbiosis, 2015)

An acenocoumarol dosing algorithm exploiting clinical and genetic factors in South Indian (Dravidian) population - Dhakchinamoorthi Krishna Kumar; Deepak Gopal Shewade; Marie-Anne Loriot; Philippe Beaune; B. V. Sai Chandran; Jayaraman Balachander; Chandrasekaran Adithan (European Journal of Clinical Pharmacology, 2015)

Unusual and rare manifestations of dengue during a dengue outbreak in a tertiary care hospital in South India - M. Neeraja; V. lakshmi; V. D. Teja; Vanjari Lavanya; E. N. Priyanka; K. Subhada; M. M. Parida; P. K. Dash; Sashi Sharma; P. V. L. Rao; Gopal Reddy (Archives of Virology, 2014)

Microsatellite Markers to Determine Population Genetic Structure in the Golden Anchovy, Coilia dussumieri - A. Kathirvelpandian; A. Gopalakrishnan; W. S. Lakra; Gopal Krishna; Rupam Sharma; K. K. Musammilu; V. S. Basheer; J. K. Jena (Biochemical Genetics, 2014)

Molecular phylogeny of elasmobranchs inferred from mitochondrial and nuclear markers - A. Pavan-Kumar; P. Gireesh-Babu; P. P. Suresh Babu; A. K. Jaiswar; V. Hari Krishna; K. Pani Prasasd; Aparna Chaudhari; S. G. Raje; S. K. Chakraborty; Gopal Krishna; W. S. Lakra (Molecular Biology Reports, 2014)

Effect of CYP2C9, VKORC1, CYP4F2 and GGCX genetic variants on warfarin maintenance dose and explicating a new pharmacogenetic algorithm in South Indian population - Dhakchinamoorthi Krishna Kumar; Deepak Gopal Shewade; Marie-Anne Loriot; Philippe Beaune; Jayaraman Balachander; B. V. Sai Chandran; Chandrasekaran Adithan (European Journal of Clinical Pharmacology, 2014)

Tidal variations in the Sundarbans Estuarine System, India - MEENAKSHI CHATTERJEE; D SHANKAR; G K SEN; P SANYAL; D SUNDAR; G S MICHAEL; ABHISEK CHATTERJEE; P AMOL; DEBABRATA MUKHERJEE; K SUPRIT; A MUKHERJEE; V VIJITH; et al. (Journal of Earth System Science, 2013)

3D-QSAR pharmacophore modeling and in silico screening of phospholipase A2α inhibitors - Shailesh V. Jain; Manjunath Ghate; Kamlendra S. Bhadoriya; Sanjaykumar B. Bari; Gopal Sugandhi; Prashant Mandwal (Medicinal Chemistry Research, 2013)

Multifarious beneficial traits and plant growth promoting potential of Serratia marcescens KiSII and Enterobacter sp. RNF 267 isolated from the rhizosphere of coconut palms (Cocos nucifera L.) - Priya George; Alka Gupta; Murali Gopal; Litty Thomas; George V. Thomas (World Journal of Microbiology and Biotechnology, 2013)

Ground-based in situ measurements of near-surface aerosol mass concentration over Anantapur: Heterogeneity in source impacts - B. S. K. Reddy; K. R. Kumar; G. Balakrishnaiah; K. R. Gopal; R. R. Reddy; V. Sivakumar; S. Md. Arafath; A. P. Lingaswamy; S. Pavankumari; K. Umadevi; Y. N. Ahammed (Advances in Atmospheric Sciences, 2013)

Analysis of full-length sequences of two Citrus yellow mosaic badnavirus isolates infecting Citrus jambhiri (Rough Lemon) and Citrus sinensis L. Osbeck (Sweet Orange) from a nursery in India - A. M. Anthony Johnson; B. K. Borah; D. V. R. Sai Gopal; I. Dasgupta (Virus Genes, 2012)

Distribution of Arbuscular Mycorrhizae Associated with Coconut and Arecanut Based Cropping Systems - K. Ambili; George V. Thomas; P. Indu; Murali Gopal; Alka Gupta (Agricultural Research, 2012)

Biological Control of Chickpea Collar Rot by Co-inoculation of Antagonistic Bacteria and Compatible Rhizobia - B. Hameeda; G. Harini; O. P. Rupela; J. V. D. K. Kumar Rao; Gopal Reddy (Indian Journal of Microbiology, 2010)

Effect of osmotic stress on plant growth promoting Pseudomonas spp. - V. Sandhya; Sk. Z. Ali; B. Venkateswarlu; Gopal Reddy; Minakshi Grover (Archives of Microbiology, 2010)

Association of a potyvirus with mosaic disease of gherkin (Cucumis anguria L.) in India - M. Srinivasulu; B. Sarovar; A. M. Anthony Johnson; D. V. R. Sai Gopal (Indian Journal of Microbiology, 2010)

Plant diversity in sacred forest fragments of Western Ghats: a comparative study of four life forms - Navendu V. Page; Qamar Qureshi; Gopal S. Rawat; Cheppudira G. Kushalappa (Plant Ecology, 2010)

Alleviation of drought stress effects in sunflower seedlings by the exopolysaccharides producing Pseudomonas putida strain GAP-P45 - V. Sandhya; Ali SK. Z.; Minakshi Grover; Gopal Reddy; B. Venkateswarlu (Biology and Fertility of Soils, 2009)

Sequencing and computational analysis of complete genome sequences of Citrus yellow mosaic badna virus from acid lime and pummelo - Basanta K. Borah; A. M. Anthony Johnson; D. V. R. Sai Gopal; Indranil Dasgupta (Virus Genes, 2009)

Amplification of Plant Beneficial Microbial Communities During Conversion of Coconut Leaf Substrate to Vermicompost by Eudrilus sp. - Murali Gopal; Alka Gupta; E. Sunil; George V. Thomas (Current Microbiology, 2009)

A Confocal microscopic study on colony morphology and sporulation of Bacillus sp. - M. S. Mary; Judy Gopal; B. V. R. Tata; T. S. Rao; S. Vincent (World Journal of Microbiology and Biotechnology, 2008)

Size segregated aerosol mass concentration measurements over the Arabian Sea during ICARB - Vijayakumar S. Nair; K. Krishna Moorthy; S. Suresh Babu; K. Narasimhulu; L. Siva Sankara Reddy; R. Ramakrishna Reddy; K. Rama Gopal; V. Sreekanth; B. L. Madhavan; K. Niranjan (Journal of Earth System Science, 2008)

Characteristics of spectral aerosol optical depths over India during ICARB - S. Naseema Beegum; K. Krishna Moorthy; Vijayakumar S. Nair; S. Suresh Babu; S. K. Satheesh; V. Vinoj; R. Ramakrishna Reddy; K. Rama Gopal; K. V. S. Badarinath; K. Niranjan; Santosh Kumar Pandey; M. Behera; et al. (Journal of Earth System Science, 2008)

Measurements of surface ozone at semi-arid site Anantapur (14.62°N, 77.65°E, 331 m asl) in India - R. R. Reddy; K. Rama Gopal; L. Siva Sankara Reddy; K. Narasimhulu; K. Raghavendra Kumar; Y. Nazeer Ahammed; C. V. Krishna Reddy (Journal of Atmospheric Chemistry, 2008)

Development of Core Subset of Finger Millet Germplasm Using Geographical Origin and Data on 14 Quantitative Traits - Hari D. Upadhyaya; C. L. L. Gowda; R. P. S. Pundir; V. Gopal Reddy; Sube Singh (Genetic Resources and Crop Evolution, 2006)

In Vitro Detoxification of Pendimethalin by Two Actinomycetes spp - M. Gopal; S. K. Jha; L. Shukla; R. V. Rawat (Bulletin of Environmental Contamination and Toxicology, 2005)

Changes in verte brate‐type steroids and 5‐hydroxytryptamine during ovarian recrudescence in the Indian spiny lobster, Panulirus homarus - Ramalingam Kirubagaran; Dassiah M. Peter; Gopal Dharani; Nambali V. Vinithkumar; Gopinathapillai Sreeraj; Muthukamatchi Ravindran (New Zealand Journal of Marine and Freshwater Research, 2005)
Vertebrate‐type steroids (estradiol‐17β and progesterone) and 5‐hydroxytryptamine (5‐HT) were examined during the different stages of ovarian maturation in the Indian spiny lobster Panulirus homarus. Estradiol‐17β and progesterone in the haemolymph and ovary were quantified by radioim‐munoassay. Estradiol‐17β was not detectable in the haemolymph when the oocytes were in stage I. It appeared in the haemolymph only as the oocytes attained stage II. Subsequently, a sharp increase in the level of estradiol‐17β was observed in the haemolymph of lobsters with stage III oocytes; it then showed a significant fall when the ovary was full of stage IV oocytes. Although progesterone was also not detectable in the haemolymph when the oocytes were in stage I, it gradually increased during stages II and III and reached a peak level during stage IV. Surprisingly, both estradiol‐17β and progesterone were detectable in the ovary from stage I onwards. In the ovary, estradiol‐17β and progesterone showed peak levels during stages III and IV, respectively. A stage‐dependent change in the activity and distribution of 5‐hydroxytryptaminergic neurons in the brain and thoracic ganglia was also observed immunocytochemically in relation to ovarian recrudescence. Furthermore, HPLC‐EC conducted on the level of 5‐HT in the brain and thoracic ganglia indicated similar changes in relation to ovarian maturation. These results strongly suggest that 5‐HT is involved in ovarian development through certain inhibitory/stimulatory factors present in the X‐organ‐sinus gland complex of the eye‐stalk in the spiny lobster P. homarus.

Recycling and Utilization of Metabolic Wastes for Energy Production is an Index of Biochemical Adaptation of Fish under Environmental Pollution Stress - K. Kamalaveni; V. Gopal; Ursula Sampson; D. Aruna (Environmental Monitoring and Assessment, 2003)

The Indian summer monsoon as revealed by the NCMRWF system - P. L. S. Rao; U. C. Mohanty; P. V. S. Raju; Gopal Iyengar (Journal of Earth System Science, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Effect of Heavy Metals on the Blood Protein Biochemistry of the Fish CYPRINUS CARPIO AND ITS USE AS A BIO-INDICATOR OF POLLUTION STRESS - V. Gopal; S. Parvathy; P. R. Balasubramanian (Environmental Monitoring and Assessment, 1997)